10(x+2)=3(x-5)

Simple and best practice solution for 10(x+2)=3(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(x+2)=3(x-5) equation:


10(x+2)=3(x-5)

We simplify the equation to the form, which is simple to understand
10(x+2)=3(x-5)

Reorder the terms in parentheses
+(+10x+20)=3*(x-5)

Remove unnecessary parentheses
+10x+20=+3+*(+x-5+)

Reorder the terms in parentheses
+10x+20=+(+3x-15)

Remove unnecessary parentheses
+10x+20=+3x-15

We move all terms containing x to the left and all other terms to the right.
+10x-3x=-15-20

We simplify left and right side of the equation.
+7x=-35

We divide both sides of the equation by 7 to get x.
x=-5

See similar equations:

| 5x-25=225 | | 6x+2x=10x+12-4 | | -8r-3(6-2r)+48=30 | | 6r=.42 | | 80-5x=8x-15 | | 3(-2/3)-4(1/2)= | | -3+6x=5x-14 | | 4(d+7)=88 | | 3a+7-5a=-11 | | 3r=1.2 | | 3w+17=8 | | 9(x-3)=16 | | -10-5x=5x-10 | | 3(p+2)+2(p-3)=-5 | | 200=a+b | | 275-5x=40x+15 | | 6x+3(4-x)=8-2(x+3) | | 13-8x=141-36x | | -7x+3(-2x-11)=-98 | | n+n-7=33 | | 2n-9=53 | | 100x-670=-670 | | (ax^3-3x^2+2bx-2)-(2x^3-cx^2-5x-4d)=x^2+x-6 | | 2x-3(4x-11)=143 | | -k+11(-k-0.01)= | | -7x+4=-3-6x | | 20x^3-120x^2=0 | | -7x+4=-3-6 | | 0.7m+0.6m=3.4 | | -8(4+g)+4=36 | | -10=2d-2 | | 0.08x-0.1=16.7 |

Equations solver categories